2016
DOI: 10.1002/tie.21852
|View full text |Cite
|
Sign up to set email alerts
|

Do Strategic Motives Affect Ownership Mode of Foreign Direct Investments (FDIs) in Emerging African Markets? Evidence from Ghana

Abstract: The objective of this study is to examine the influence of ownership, location, and internalization‐specific factors, as well as strategic motives on ownership choice of foreign subsidiaries in Ghana. The authors use a quantitative methodology in order to statistically explore the relationships between dependent and independent variables by using the logistic regression model. The analysis was based on 115 manufacturing investments made by multinational corporations (MNCs) from different countries in 1994–2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 67 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…A firm derives ownership advantage abroad relative to local firms when it has a differentiated product with some degree of market power or cost advantage and engages in FDI, which becomes the basis for intra‐firm trade. A recent study by Ato Dadzie, Afriyie Owusu, Amoako, and Aklamanu () discusses at length strategic motives for the ownership mode of FDI. Location advantage to the firm arises from unique advantages of production abroad relative to home country in the form of proximity to raw materials and/or markets, lower cost labor, and the like.…”
Section: Oli Frameworkmentioning
confidence: 99%
“…A firm derives ownership advantage abroad relative to local firms when it has a differentiated product with some degree of market power or cost advantage and engages in FDI, which becomes the basis for intra‐firm trade. A recent study by Ato Dadzie, Afriyie Owusu, Amoako, and Aklamanu () discusses at length strategic motives for the ownership mode of FDI. Location advantage to the firm arises from unique advantages of production abroad relative to home country in the form of proximity to raw materials and/or markets, lower cost labor, and the like.…”
Section: Oli Frameworkmentioning
confidence: 99%
“…Our systematic review revealed four studies on the reasons that foreign firms enter Africa through IJVs (Boateng & Glaister, 2003;Dadzie et al, 2018;Luiz & Charalambous, 2009;Odediran & Windapo, 2017).…”
Section: Ijv Entry Decisions and Entry Motives Into Africamentioning
confidence: 99%
“…Thus, we propose the following: Strategic assets are concentrated in the developed economies (Makino, Lau, & Yeh, 2002). For this reason, we will continue to see IJVs with market-seeking and efficiency-seeking motives in Africa (Dadzie et al, 2018). While foreign partners will continue to pursue these motives, local partners will continue their efforts to acquire technological skills and management expertise from foreign partners.…”
Section: Propositionsmentioning
confidence: 99%
See 2 more Smart Citations